2015
DOI: 10.1177/0885328215577296
|View full text |Cite
|
Sign up to set email alerts
|

Dental pulp tissue engineering with bFGF-incorporated silk fibroin scaffolds

Abstract: The clinical translation of regenerative endodontics demands further development of suitable scaffolds. Here, we assessed the possibility of using silk fibroin scaffold for pulp regeneration with dental pulp stem cells (DPSCs) and basic fibroblast growth factor (bFGF) in ectopic root canal transplantation model. Porous silk fibroin scaffolds were fabricated using freeze-drying technique (with or without bFGF incorporation), and characterized by scanning electron microscopy (SEM) and Fourier transform infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 36 publications
1
45
0
1
Order By: Relevance
“…Some carriers that have previously been proposed were collagen (Hu et al 1998, Kikuchi et al 2007, Bezerra Da Silva et al 2008, gelatin Ishimatsu et al 2009), agarose (Chaussain et al 2009), sodium alginate (Oliva-Rodriguez et al 2011), chitosan . Current in vitro evidence suggests other potential drug delivery systems for bioactive molecules, such as biodegradable polymer matrix of lactide and glycolide (Mathieu et al 2013), porous silk fibroin scaffolds (Yang et al 2015), poly-2-hydroxyethyl methacrylate (polyHEMA)-based hydrogel (Takeda et al 2015), tricalcium phosphate microsphere-hydrogel composite (Lee et al 2014). In addition, biomaterials that can be used as scaffolds for VPT have recently been suggested and could enhance proliferation and differentiation of human dental pulp cells, such as polycaprolactone/submicron bioactive glass hybrid composites (Wang et al 2016a), a chitosan-based scaffold (Bellamy et al 2016) and keratin hydrogel (Sharma et al 2016).…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%
“…Some carriers that have previously been proposed were collagen (Hu et al 1998, Kikuchi et al 2007, Bezerra Da Silva et al 2008, gelatin Ishimatsu et al 2009), agarose (Chaussain et al 2009), sodium alginate (Oliva-Rodriguez et al 2011), chitosan . Current in vitro evidence suggests other potential drug delivery systems for bioactive molecules, such as biodegradable polymer matrix of lactide and glycolide (Mathieu et al 2013), porous silk fibroin scaffolds (Yang et al 2015), poly-2-hydroxyethyl methacrylate (polyHEMA)-based hydrogel (Takeda et al 2015), tricalcium phosphate microsphere-hydrogel composite (Lee et al 2014). In addition, biomaterials that can be used as scaffolds for VPT have recently been suggested and could enhance proliferation and differentiation of human dental pulp cells, such as polycaprolactone/submicron bioactive glass hybrid composites (Wang et al 2016a), a chitosan-based scaffold (Bellamy et al 2016) and keratin hydrogel (Sharma et al 2016).…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%
“…seeded 2×10 6  DPSCs/per silk fiber/collagen/hexafluoro-2-propanol (HFIP) scaffold and observed that they formed soft dental pulp. 65 However, the disadvantages associated with these cells is their heterogeneity which can affect its osteogenic potential. Moreover, several investigators have also reported the limited potential of DMSCs to regenerate bone in vivo due to its inability to promote de novo bone formation in the form of cortical bone and not vascularized bone as noted in a human mandibular defect.…”
Section: Stem Cells In Bone Regenerationmentioning
confidence: 99%
“…These therapies explore the endogenous regenerative potential of the endodontic tissues and procure to enhance it by combining biopolymers with adequate biochemical stimuli [1]. Among the most reported biopolymers for endodontic therapy are hyaluronic acid (HA) [2][3][4], chitosan [5], alginate [6], gelatin [7][8][9], collagen [10,11], fibrin [12], and silk fibroin [13]. These natural-origin molecules resemble the extracellular matrix (ECM) components, providing unique properties to the specific regenerative approach, thereby enhancing their biocompatibility and biological recognition.…”
Section: Introductionmentioning
confidence: 99%